Impact of brassinosteroids on biochemical parameters of papaya (Carica papaya L. cv. Red Lady.) under salt stress - Aarti, D; Shivani, D; Manish, B; Ravindra, S; Komal, S; Rajesh, J; Lokesh, T H; Rupesh, K; Kumar, Rajneesh (Plant Science Today, 2026)
In fruit orchards, the excessive use of NaCl caused significant plant physiological stress and a decline in soil health. In order to counteract the negative effects of salinity stress, the current study was carried out in 2024 to assess how foliar spraying with brassinosteroids (BRs) affected the rate of expansion and biochemical functioning of Carica papaya L. cv. Red Lady. In fruit orchards, brassinosteroid foliar sprays were applied at concentrations of 0.05, 0.1 and 0.2 mg L-1 in combination with salinity treatments of 150, 200 and 250 mM NaCl, along with an untreated control. A number of physiological and biochemical parameters were evaluated in the study, such as membrane stability index, injury index, anthocyanin and carotenoid contents, proline accumulation, catalase activity, total chlorophyll, chlorophyll a, chlorophyll b and chlorophyll a/b ratio. The application of brassinosteroid was found to significantly mitigate the adverse consequences of salinity stress, as evidenced by better pigment and osmolyte levels as well as increased antioxidant enzyme activity. Biochemical parameters improved most noticeably with 0.1 mg L-1 and 0.2 mg L-1 BR in combination with 200 mM NaCl among the treatments. According to the research, papaya’s ability to withstand salt can be successfully increased by foliar implementation of brassinosteroids, especially at 0.1 mg L-1, which improves antioxidative defence and preserves membrane stability.